Governing the Justice System : Spain's Judicial Council - Lopez Guerra, Luis (World Bank, Washington, DC, 2012)
Following the European model, many developing, and transitional economies have established councils, independent of other government branches to govern their judiciaries. Spain's experience illustrates the issues raised by the creation, and operation of these entities. It's Constitution states that the Council is to consist of the president of the Supreme Court who presides over it, plus twenty individuals, each of whom serves for five years. It is further required by the Constitution, that eight members from outside the judiciary be appointed by a three-fifths majority of Parliament. Nonetheless, the country's diverse political camps have differed on the methods for selecting members for the judiciary: opponents of election by judges cite potential ideological confrontations within the judiciary, and, the possible tendency to emphasize the interests of those who elected them is another factor. While experience suggests there is no single right answer to the selection of Council members, it does point to a broader latitude in election decisions. The note thus examines the core functions of the Council, as specified by the Constitution. Though not a court, the Council tasks are managerial, and administrative, and, develops and implements policies relating specifically to the organization of the judiciary.